From Web to Cyborg Tracing Power in Care - Coble, Richard (2016)
Late into my eight and a half hour shift as a hospital chaplain, the paper tally I keep in my breast pocket says that I have had only fifteen visits today. My goal is nineteen, given the pressure from administration to boost our office's coverage and increase the number of electronic forms we log into the interdisciplinary chart. The next visit initially appears to be a quick one. A middle-aged woman in a hospital gown greets me cautiously as I knock and enter. Perhaps because the patient is intuiting my fatigue or is just too tired to talk, she responds to my questions with one word answers: She feels "fine"; her stay has been "good"; she feels "ready" to leave to hospital "soon." At the end of a long day, with a few more to go, I feel this visit going nowhere beyond these surface-level greetings, and I am ready to leave a few minutes into the conversation. I ask the patient if she would like prayer. She nods but does not voice any immediate concerns, so I pray for God's accompanying and loving presence to be felt in the room as the patient finishes her hospital stay, a version of the same prayer I say with most patients. Yet, when I open my eyes, thinking this quotidian, going-through-the-motions visit is over, there are tears in the woman's eyes. She wipes them away sheepishly, and when I inquire about them, she tells me of the loneliness she has felt recently. We speak briefly of troubled relationships and the felt distance from loved ones being exacerbated by uncomfortable days in the hospital. She smiles appreciatively as I leave. In the hallway, as I remove my notes and draw a new mark on my sheet, I pause. That brief encounter, the sudden and unexpected meaning at the end - it is poignant encounters like this that keep bringing me back to the hospital. So much subtle meaning is condensed into a sixteenth mark of the pen made before I move on to the next visit. I have three more, so I had better keep moving. Such is cyborg ministry.